Measurement of photoelectron generation in a gold coated glass slide - Almugren, K.S.; Abdul Sani, S.F.; Uguru, E.H.; Amiera Narissa, N.H.; Zakaria, R.; Alkallas, F.H.; Bradley, D.A. * (Elsevier, 2021)
In thin low-Z media irradiated by photon energies of several tens of keV, the presence of a high-Z additive can result in manifest locally modified secondary electron dose. Present study analyses the photoelectron dose enhancement resulting from nanometre thickness gold (atomic number Z = 78) coated on commercial borosilicate (B2O3) glass microscope cover-slips. Two thicknesses of B2O3 cover-slip have been utilized, 0.13 ± 0.02 mm and 1.00 ± 0.01 mm, with single-sided Au coatings of 20, 40, 60, 80 and 100 nm. An additional uncoated glass slide has been kept as a comparator. The samples have been exposed to X-rays generated at kVp potentials, delivering a fixed dose of 2 Gy. Dose enhancement resulting from the 1.00 mm glass has been observed to be ~1.32 × that of the 0.13 mm thickness glass. The elemental composition of the samples has been obtained via Electron Dispersive X-ray (EDX), elemental content differences between the two thicknesses of glass leading to a difference in effective atomic number of less than 0.3%. The influence on photon yield of the gold coating and variations in elemental content has been modelled using Monte Carlo simulation, allowing comparison with the measured values of enhanced TL yield.